An emerging cosmotheandric religion? : Raimon Panikkar's pluralistic theology of religions - Komulainen, Jyri. (Studies in Christian Mission, 2005)
Raimon Panikkar (b. 1918), a Catalan-born Hindu-Christian, is a prominent theorist of interreligious dialogue. This study gives a detailed analysis of his theology of religions. On the basis of the most recent sources available, it appears that even his "radical pluralism" cannot eschew the inherent problems characteristic of pluralistic theologies of religions. Unlike other pluralists, Panikkar does not subscribe to the Enlightenment tradition. Instead, his plea for the transformation of existing religions is based on an idiosyncratic "cosmotheandrism," which draws on both primordial religious traditions and existentialist philosophy. The prerequisites of interreligious dialogue, as outlined in his work, thus entail commitment to a particular cosmology and mode of consciousness.